Pengaruh Media Papan Pintar Terhadap Hasil Belajar Pelajaran Pancasila Siswa Kelas I SD Negeri Bajardowo 2 - Siti Roudhotul Jannah; Putri Dwi Ardianti; Derby Ahliyanto; Rizka Nur Aminah; Siti Robiah Al-Adawiyah; Usfina Kholidah Izah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Abstrak. Learning media are crucial to educational activities because they help professors convey abstract concepts more easily and also help students pay more attention and feel more engaged. Based on the above problem background explanation, the goal of this study is to ascertain the extent to which smart board media enhances the learning outcomes of first-graders at SDN Negeri Banjardowo 2 in Pancasila lessons on symbol material and the application of Pancasila principles. This study will employ a quantitative research design as its research methodology. Pre-experimental design using the one-group pretest-posttest design paradigm is the methodology employed. According to the study's findings, using smart board media improved the continuous learning process. Teachers may provide more engaging and diversified content by utilizing smart board media. Because the learning principle is learning while playing, the class may be made lively and fun with the use of this smart board media.